Sri Aurobindo as ‘A Truth – Bearer’ And ‘A Singer of Beauty’: An Appraisal: Exploring the Poetic Vision of Sri Aurobindo (Journal of Advances and Scholarly Researches in Allied Education, 2017)
This article lays focus on the poetic forte and vision of the universally acknowledged writer sri. Aurobindo, especially his love poems with a touch of immortality and perfection. It examines how he has presented a youthful vitality combined with an intense love of life and it may be said that being a singer of beauty, sri Aurobindo stands as a model of his own belief that a poet is a ‘truth – bearer’ and ‘beauty – singer’.It is universally acknowledged that Sri Aurobindo represents “the return of the Rishi”, the orphic voice of the poet in the modern chaotic world. Scholars, philosophers, man and men whose minds are nourished with enlightenment and supreme knowledge do find in him the promise of the superman, the profounder of Integral yoga, the prophet of the Life Divine, while others look upon him as the prophet of peace and the fiery evangelist of Nationalism. There are still others who look upon him as a teacher, scholar, interpreter of the Vedas, critic of life, man of letters in excelsis, master of prose, great dramatist and excellent poet of great power and vision.